The Macroeconomic Impact of Healthcare Financing Alternatives : Reform Options for Hong Kong SAR. (IMF Working Papers; Working Paper, 2008)
With much healthcare publicly funded, Hong Kong's rapidly aging population will significant raise fiscal pressure over coming decades. We ask what the implications are of meeting these costs by public funding, or private funding voluntarily or through mandates. Our simulations suggest that without early reform, these costs quickly become unsustainable. Prefunding is key. Whether this is done through the public system or through mandatory private provision is less important. Voluntary schemes are likely to result in insufficient savings without tax incentives. Even then, voluntary accounts are unlikely to yield better macroeconomic outcomes, while mandates tend to produce more equitable consumption.